(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
The pathological processes of primary open-angle glaucoma is unknown. Several studies show the relation between Helicobacter pylori infection and primary open-angle glaucoma. The purpose of this study was to assess the association between H. pylori infection and primary open-angle glaucoma. Forty patients of diagnosed primary open-angle glaucoma were selected as case and 40 participants without primary open-angle glaucoma were selected as control as per inclusion and exclusion criteria. Complete clinical evaluation including history, physical examination, relevant ocular examinations and laboratory investigations were performed. Serologic evidence of H. pylori infection was found in 75% of patients with primary open-angle glaucoma and 30% of patients without primary open-angle glaucoma which achieved statistically significant difference (p=0.000, OR=7.00 and CI 95% =2.61-18.74). 13C urea breath test was positive in 70% in case group and 37.5% in control group which also achieved statistically significant difference (p=0.003, OR=3.89 and CI 95% =1.53-9.87). The findings revealed significant association between H. pylori infection and primary open-angle glaucoma.